Local area concept plan for Tobago - Halcrow Group (Trinidad and Tobago). (Halcrow Group (Trinidad and Tobago)., 2011)
Presents the development plans for Tobago, with descriptions of the areas, development issues and opportunities, land uses and development proposals for various location in Tobago, with infrastructural development plans.
Keywords: Physical planning – Tobago, Infrastructure – Tobago, Land use, Land development, Urban development, Transportation.